Perancangan Alat Bantu Cuci Tangan Dengan Teknologi Sederhana [Pedal Kaki] - Candra Prilyanto (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
The Covid-19 pandemic, which also hit Indonesia, had a significant impact on all levels. The spread of this virus through the splashes of Covid-19 sufferers from the nose, and mouth, when coughing, sneezing, or breathing. This spark attached to objects, and surrounded surfaces, and held by other people, enter the body through the eyes, nose, mouth. Hand wash was important, simple, and effective in the process of preventing disease transmission. The aim of this research made a hand wash tool, when it was used, the hand did not touched the soap bottle and water faucet. The method was the literature study method, the observation method, and the experimental method with a tool design model. Design concept was carried out in accordance with the process, start from the initially sketch, concept selection, value analysis, to made prototype and experiments. Results and conclusions obtained from this experiment of this tool were the smooth process of getting out of water and soap on average less than 2 times the footing. And validation shows okay, which means that the design of this hand washed tool accordance with the specifications of the needs of the customer or user.